2004
DOI: 10.1152/ajpgi.00260.2003
|View full text |Cite
|
Sign up to set email alerts
|

Coactivation of capacitative calcium entry and L-type calcium channels in guinea pig gallbladder

Abstract: We have evaluated the presence of capacitative Ca2+ entry (CCE) in guinea pig gallbladder smooth muscle (GBSM), including a possible relation with activation of L-type Ca2+ channels. Changes in cytosolic Ca2+ concentration induced by Ca2+ entry were assessed by digital microfluorometry in isolated, fura 2-loaded GBSM cells. Application of thapsigargin, a specific inhibitor of the Ca2+ store pump, induced a transient Ca2+ release followed by sustained entry of extracellular Ca2+. Depletion of the stores with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
45
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 45 publications
8
45
0
Order By: Relevance
“…Furthermore, we have previously demonstrated that VDCC and nonselective cation channels in the plasma membrane (27,30,33,54) and the SR (2,3,27,34) are also essential for rhythmic activity in the GBSM. Collectively, these findings indicate that the mitochondrion, SR, and plasma membrane channels constitute key components of the GBSM pacemaker.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we have previously demonstrated that VDCC and nonselective cation channels in the plasma membrane (27,30,33,54) and the SR (2,3,27,34) are also essential for rhythmic activity in the GBSM. Collectively, these findings indicate that the mitochondrion, SR, and plasma membrane channels constitute key components of the GBSM pacemaker.…”
Section: Discussionmentioning
confidence: 99%
“…The cell length was similar in the three age groups (young adult 44.68 Ϯ 1.62, aged 45.49 Ϯ 1.83, and melatonin 43.07 Ϯ 1.36 m; n ϭ 98, 61, and 96 cells, respectively) Cell Loading and [Ca 2؉ ] i Determination. [Ca 2ϩ ] i was determined by epifluorescence microscopy using the fluorescent ratiometric Ca 2ϩ indicator fura 2 as described previously (Morales et al, 2004). Isolated cells were loaded with 4 M fura 2/AM at room temperature for 25 min.…”
Section: Methodsmentioning
confidence: 99%
“…at ASPET Journals on May 11, 2018 jpet.aspetjournals.org capacitative calcium entry (CCE) is another influx route activating contraction in gallbladder smooth muscle (Morales et al, 2004). As previously reported, after depletion of the stores by incubation of control gallbladder strips with 1 M TPS in Ca 2ϩ -free medium for 30 min, reintroduction of extracellular Ca 2ϩ induced a sustained contraction (3.69 Ϯ 0.53 mN/mg; n ϭ 12) that was significantly smaller in aged strips (2.68 Ϯ 0.29 mN/mg; n ϭ 9, P Ͻ 0.01) but similar in melatonin-treated animals (4.41 Ϯ 0.39 mN/mg; n ϭ 8) (Fig.…”
Section: Melatonin and Aged Gallbladder 851mentioning
confidence: 99%
“…Another Ca 2 þ influx pathway that contributes to the CCKinduced gallbladder contraction is the activation of CCE mechanisms (Morales et al, 2004). To test whether cAMP could affect this pathway, CCE was activated by depletion of the stores with thapsigargin in a free Ca 2 þ medium and then Ca 2 þ was restored in the extracellular medium in the presence of 1 mM nitrendipine to block non-CCE.…”
Section: S Morales Et Almentioning
confidence: 99%
“…Recently, CCE, which has been shown to be essential in nonexcitable cells (Putney, 1986), is gaining attention in the area of smooth muscle physiology (Gibson et al, 1998) where it participates in contraction (Morales et al, 2004). However, the possible role of cAMP controlling this process remains unknown.…”
Section: S Morales Et Almentioning
confidence: 99%